Physical Activity and Functional Disability Among Older Adults in Ghana: The Moderating Role of Multi-Morbidity - Villalobos-Dintrans, P (Public Library of Science, 2023)
Knowledge about how physical activity levels relate to functional disability is essential for health promotion and planning older adults care or rehabilitation. The risk of living with one or more chronic health conditions increases with increasing age in lower and higher income countries-many of which are associated with physical inactivity. We conducted a cross-sectional study to examine the moderating role of multimorbidity on physical activity and its measures on functional disability among older adults in Ghana. Data from WHO s Study on global AGEing and adult health Ghana Wave 2 with a sample of 4,446 people aged 50+ years was used for this study. Functional disability was assessed using the 12-item WHO Disability Assessment Schedule 2.0. Three categories of physical activity levels were used: vigorous intensity, moderate intensity, and walking. Past month diagnosis by a doctor was used to assess the presence of a chronic condition, and the presence of two or more conditions was used to define multi-morbidity. Logistic regressions with a post hoc interactional tests were used to examine the associations. Overall, physical activity had a significant association with functional disability (OR = 0.25, 95%CI; 0.12, 0.32). A similar relationship was found for vigorous-intensity (OR = 0.19, 95%CI: 0.12, 0.29), moderate-intensity (OR = 0.19, 95%CI: 0.15, 0.25) and walking (OR = 0.41, 95%CI: 0.33, 0.51). Older adults living with one condition and physically active were 47% less likely to experience functional disability compared with the less active counterparts living with at least two chronic conditions. Among the three measures of physical activity, multimorbidity moderated the relationship between walking and functional disability. Future strategies for meeting the health and longterm care needs of older adults, particularly those living with only one chronic condition in Ghana should consider encouraging walking. Policies, financial assistance, family, and community level interventions aimed to promote and sustain physical activity among older adults should be a priority for stakeholders in Ghana. © 2023 Awuviry-Newton et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.